Synthesis and Characterisation of Penta-Bismuth Hepta-Oxide Nitrate, Bi5O7NO3, as a New Adsorbent for Methyl Orange Removal from an Aqueous Solution - Eshraq Ahmed Abdullah; Abdul Halim Abdullah; Zulkarnain Zainal; Mohd Zobir Hussein; Tan Kar Ban (E-Journal of Chemistry)
This paper presents the synthesis of penta-bismuth hepta-oxide nitrate, Bi5O7NO3, via the chemical precipitation method. After calcination, the precipitate was characterised by several methods, which included X-ray powder diffraction, X-ray photoelectron spectroscopy, scanning and transmission electron microscopy, Fourier transform infrared, thermogravimetric analysis, BET surface area and pH drift method to determine the pH of point of zero charge (pHpzc). The study results revealed that Bi5O7NO3 had an orthorhombic crystal structure, a surface area of 1.6 m2 g-1 and a point of zero charge at pH 9.7. The chemical state of Bi5O7NO3 indicated the presence of three oxidation states of bismuth centre. Furthermore, the decolourization ability of Bi5O7NO3 to remove the azo dye was also evaluated. Although it had lower surface area, the removal efficiency was extremely good. This finding suggests that Bi5O7NO3 could be used as a promising adsorbent for azo dye removal. The XPS spectra showed that the accumulation of dye onto Bi5O7NO3 could be due to the anion exchange process, suggesting the birth of a new anion exchanger for azo dye removal.